Unveiling the IL-1β/CXCL2 axis: a shared therapeutic target in periodontitis and inflammatory bowel disease - Gu, Zhongyi; Gao, Aichao; Ma, Xiang; Wang, Xiaotong; Zhang, Yi; Wang, Yucun; Qiu, Caiqing (Frontiers in Immunology, 2026)
BackgroundPeriodontitis is clinically associated with inflammatory bowel disease (IBD), yet the shared cellular and molecular programs underpinning this oral–gut inflammatory link remain incompletely defined.MethodsWe integrated bulk gingival transcriptomes from two periodontitis cohorts (GSE16134 and GSE10334) with single-cell RNA-seq data from IBD patients (51,322 cells, 18 samples). After standard quality control and batch-aware integration, we performed pseudobulk differential expression gene (DEG) analysis at the patient level to identify IBD-associated genes and intersected these with periodontitis-consensus DEGs to derive shared signatures. Cell-cell communication networks were inferred using CellChat, and gene set enrichment analysis were conducted to delineated inflammatory signaling. Myeloid subpopulations further resolved to characterize disease-associated functional states. Key findings were assessed in a dual-inflammation rodent model by immunohistochemistry.ResultsWe identified 188 common DEGs across the two periodontitis cohorts and 66 genes shared in IBD, which were predominantly enriched in immune compartments and motivated a focused analysis of myeloid cells. Communication analysis revealed extensive network remodeling in IBD, with myeloid populations acting as major signaling hubs. Myeloid subclustering highlighted inflammatory and chemokine-related states characterized by high IL1B expression. Among chemokines, CXCL2 was prioritized because it showed consistent upregulation across bulk periodontitis transcriptomes and IBD myeloid states, and it aligned with prominent IL-1β–chemokine signaling routes inferred from intercellular communication. In vivo, IL-1β and CXCL2 signals were increased in the dual-inflammation model, supporting cross-disease consistency of this axis.ConclusionsOur integrative analyses identify a shared, myeloid-centered IL-1β/chemokine inflammatory program across periodontitis and IBD, which may contribute to the oral–gut inflammatory axis. The IL1β–CXCL2 pathway represents a potentially targetable signaling module, although functional blockade studies are required to establish therapeutic causality.